A new karyotype of oligoryzomys (sigmodontinae, rodentia) from central Brazil - De S. Lima, J. Fernando (2003)
A new karyotype of the genus Oligoryzomys was described for specimens collected in Brazilian Cerrado in Tocantins and Goias States. Conventional staining, G-, C-banding, and Ag-NOR staining techniques were used for describe this karyotype with 2n = 70, AN = 74 or 76. The chromosome complement, with the highest diploid number known among Oligoryzomys species, differs from all others previously reported. This small sized Oligoryzomys species can be differentiated from other Brazilian Oligoryzomys not only by chromosomal complement, but also in some morphological attributes. The new species is apparently restricted in distribution and endemic of Brazilian Cerrado, occurring only in Rio Tocantins basin.